2015
DOI: 10.3389/fncel.2015.00198
|View full text |Cite
|
Sign up to set email alerts
|

ASK1 modulates the expression of microRNA Let7A in microglia under high glucose in vitro condition

Abstract: Hyperglycemia results in oxidative stress and leads to neuronal apoptosis in the brain. Diabetes studies show that microglia participate in the progression of neuropathogenesis through their involvement in inflammation in vivo and in vitro. In high-glucose-induced inflammation, apoptosis signal regulating kinase 1 (ASK1) triggers the release of apoptosis cytokines and apoptotic gene expression. MicroRNA-Let7A (miR-Let7A) is reported to be a regulator of inflammation. In the present study, we investigated wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 111 publications
2
19
0
Order By: Relevance
“…The ASK1/p38 signaling pathway via TLRs is critical for chemokine production and promotes inflammation and neurotoxicity after multiple sclerosis ( Guo et al, 2010 ). In line with studies that have demonstrated that ASK1 inhibition attenuates pro-inflammatory cytokines in microglia, ASK1 was found to be associated with TNF-α and iNOS production in primary microglial cell culture, and M1 macrophage suppression by a Class A scavenger receptor resulted in reductions of IL-6, IL-1β, and TNF-α, decreasing ASK1/p38/NF-κB pathway signaling, under pathologic conditions ( Hu et al, 2011 ; Katome et al, 2013 ; Song and Lee, 2015 ). Previous reports have shown that inhibition of ASK1 reduces M1 phenotype after injury and ASK1 also played a role in our results.…”
Section: Discussionsupporting
confidence: 81%
“…The ASK1/p38 signaling pathway via TLRs is critical for chemokine production and promotes inflammation and neurotoxicity after multiple sclerosis ( Guo et al, 2010 ). In line with studies that have demonstrated that ASK1 inhibition attenuates pro-inflammatory cytokines in microglia, ASK1 was found to be associated with TNF-α and iNOS production in primary microglial cell culture, and M1 macrophage suppression by a Class A scavenger receptor resulted in reductions of IL-6, IL-1β, and TNF-α, decreasing ASK1/p38/NF-κB pathway signaling, under pathologic conditions ( Hu et al, 2011 ; Katome et al, 2013 ; Song and Lee, 2015 ). Previous reports have shown that inhibition of ASK1 reduces M1 phenotype after injury and ASK1 also played a role in our results.…”
Section: Discussionsupporting
confidence: 81%
“…In the studies on let-7a in LPS-treated microglial BV2 cells, let-7a level is found to be remarkably decreased; however, let-7a overexpression can reduce the production of inducible nitric oxide synthase (iNOS) and IL-6, while promoting anti-inflammatory genes at the same time in microglia (68). Consistent with this finding, let-7a can strongly inhibit the expression of inflammatory cytokines by controlling the activation of apoptosis signal-regulating kinase 1 (ASK1), thus activating anti-inflammatory cytokines such as IL-10 and Mycs in microglia (69). Meanwhile, let-7 could act as a regulator of microglial function during inflammation and be a novel target for enhancing the beneficial function of microglia in CNS disorders.…”
Section: The Modulation Role Of Neuroinflammation In Admentioning
confidence: 65%
“…Many studies have identified specific miRNAs expression profiles of diabetes and described the critical roles of miRNAs in insulin secretion [ 21 , 22 ], pancreatic development and function [ 22 ] and diabetic cardiovascular complications [ 23 ]. However, the role of several miRNAs, such as miR-21, -146a [ 24 , 25 ] and let7A [ 26 ] as regulators in inflammation and oxidative stresses has been reported.…”
Section: Discussionmentioning
confidence: 99%